Cold chain database development and application as a tool for the cold chain management and food quality evaluation. (April 2015) - Gogou, E.; Katsaros, G.; Derens, E.; Alvarez, G.; Taoukis, P.S.
Abstract: Cold chain management can optimize freshness and safety to the consumer end. Within FRISBEE European project (http://frisbee-project.eu ) a web-based platform was developed for temperature conditions data collection throughout the chilled and frozen food supply chain. Data including all cold chain stages (industry, distributors, retailers and consumers), were collected. This extensive database comprising more than 14, 000 time-Temperature (t–T) profiles can serve as a valuable Cold Chain Management tool. The user can define a sequence of cold chain stages for selected food products. The Cold Chain Predictor (CCP) software based on the Cold Chain Database (CCD) allows calculation of product shelf-life status at different cold chain stages based on existing or user defined kinetic data. Conducted field tests expanded the Cold Chain Database and validated the software. The developed tools offer the potential to run simulation scenarios based on real cold chain data and contribute to effective cold chain improvement and management. Highlights: Cold Chain Database gives insights into the real cold chain temperature conditions. Predictive modeling along with cold chain data allows product shelf life estimation. Real cold chain temperature profiles were obtained from conducted field tests in Europe.